The Role of Transformational Leadership in Improving Employee Psychological Wellbeing: A Review - Ausat, Abu Muna Almaududi; Muhammad Aqib Shafiq; Doaa Wafik; Norma Angélica Santiesteban López (Apollo: Journal of Tourism and Business, 2024)
Employee psychological well-being is crucial in today's complex and ever-changing corporate environment. This is because technological advances, international competition, and changing consumer expectations have changed the labour market. This study aims to examine the role of transformational leadership in improving employees' psychological well-being. This research is a descriptive qualitative study that explores previous studies related to transformational leadership and employee psychological well-being. First, relevant studies were collected related to transformational leadership and employee psychological well-being and the possible impact of both constructs. After that, the author summarises the relevant studies and discusses the concepts of transformational leadership and employee psychological well-being and how they can be used in organisations. The next step is to express the author's views on the potential of transformational leadership and employee psychological well-being in organisations. Study results show that transformational leadership improves employee psychological well-being. Transformational leaders inspire and motivate their people, making them feel valued and invested in the company's objective. This boosts workplace motivation, self-esteem, and growth